Knowledge and attitude toward Middle East respiratory syndrome coronavirus among heath colleges' students in Najran, Saudi Arabia - Alqahtani, Ali Saeed (International Journal Of Community Medicine And Public Health, 2017)
Background: Najran area, Saudi Arabia, has experienced infection of Middle East Respiratory Syndrome (MERS) coronavirus. Knowledge towards prevention and control of the disease is necessary among the health colleges' students as they are at high risk of newly emerging diseases. The present study aimed to investigate the knowledge and attitude of undergraduate health colleges’ students in Najran University, Saudi Arabia towards MERS coronavirus. Methods: A structured questionnaire on MERS was developed by the researcher with the help of existing literatures to cover the survey objectives. From five health colleges, 418 health colleges’ students were invited to fill the questionnaire from February 2017 to April 2017 and statistic was used to summarize the responses. Results: The students were highly aware about the clinical aspects of MERS including diagnosis, treatment, transmission and preventive measures. However, there were statistically significant differences (p<0.05) among health colleges’ students regarding their understanding of the basic science of the virus. The students showed positive attitude about MERS and the majority indicated that they are in need for further education about it. Conclusions: The students were knowledgeable about the clinical aspects of MERS but were lacking background awareness in the basic sciences and there is need for further education and training programs.